FEATURES OF MODERN DEVELOPMENT AND PROSPECTS OF CRYPTOCURRENCY - Tkach , O.V. (The actual problems of regional economy development, 2018)
The modern terms and conditions of the crypto currency cycling are the subject of discussion in the vertical orient and scientists as for its development. The topic of this publication is a research of the terms and conditions as well as crypto currency cycling. The basic terms of crypto currency issuing and mining principals were analyzed. The crypto currency influence towards world financial system has been submitted in the present article.